Development of Large Numbers Factorization Algorithm - Illiashenko, Oleg; Pevnev, Vladimir (2019 10th IEEE International Conference on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applications (IDAACS), 2019)
The paper analyzes existing factorization algorithms and classifies them. The elaboration of the factorization algorithm which allows working with both small and large numbers is presented. Whereas the replacement of operations of addition and multiplication by the operation of addition, in comparison with the existing algorithms, a large gain of time is achieved. The initiation of operation of inequality solution allows cutting up to N 1/4 of possible candidates for a single calculation step. The evaluation of the time of the algorithm was conducted. It is comparable to the best known.